THE ROLE OF MAGNETIC RESONANCE IMAGING FOR ACUTE ISCHEMIC STROKE - Sanak, Daniel; Horak, David; Herzig, Roman; Hlustik, Petr; Kanovsky, Petr (Biomedical papers, 2009)
Background: Although computed tomography (CT) is still considered to be the gold standard of brain imaging before thrombolysis, new reperfusion strategies in acute ischemic stroke lead to more extensive use of magnetic resonance imaging (MRI).Methods and results: Diffusion- (DWI) and perfusion-weighted (PWI) MRI with MRI angiography are considered the most important examinations in diagnosis of acute ischemic stroke before reperfusion therapy. The effort to extend strict therapeutic time window resulted in the PWI/DWI mismatch concept, established to identify the presence of ischemic penumbra. Nevertheless, a lack of standards for methodology and analysis and existence of different alternative interpretations of such mismatch still present significant limitations of its use in routine clinical practice.Conclusion: MRI allows accurate diagnosis of the infarct lesion, detection of cerebral arterial occlusion or significant stenosis with evaluation of actual collateral flow and may also display certain reversible ischemic changes. However, the main objective for MRI still remains: improvement of non-invasive rapid and accurate identification of brain tissue at risk for infarction, which may be salvaged by safe and effective reperfusion therapy.
Keywords: Ischemic stroke/Thrombolysis/Magnetic resonance imaging/Mismatch